DEVELOPMENT AND VALIDATION OF SELF-CARE STATEGY SURVEY IN THE LATVIAN ADULT SAMPLE - Mārtinsone, Aleksandra Karlīna; Perepjolkina, Viktorija; Ruža, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Restrictions caused by the Covid-19 pandemic are not only known to affect communication but also to threaten people’s physical and mental health. Self-care is an important method for reducing these threats. The aim of this study was to develop a multidimensional Self-Care Questionnaire, focusing primarily on psychological care providers. The questionnaire was developed in three stages: 1. After analysis of the literature and published interviews with professionals, 172 self-cares strategies were identified and grouped into 11 main topics; 2. items were generated and a content validity of each item was evaluated by 8 experts; 3. 76 items were included in the questionnaire, which was complede by 779 participants. Participants evaluated importance and attainability of subjective self-care activities using four-point Likert scale. The main score for each activity was computed by multiplying the indicator of the first part by the indicator of the second part. Based on the series of sequental Explanatory actor Analysis, the best performing 63 items were selected and a 14-scale structure of the questionnaire were obtained. All items had acceptable psychometric properties and all scales were internaly consistent, with exception of one scale “Amusement” which did not have acceptable internal consistency. The obtained 14-factor structure were confirmed by results of the Confirmatory Factor analysis showing good to acceptable model fit. The developed questionnaire can be a useful tool for exploring and evaluating self-care strategies and can be used for both research and psychological assessment purposses, as well as for self-assessment and self-monitoring purposes.